TINJAUAN YURIDIS HUBUNGAN PEMERINTAH PUSAT DAN DAERAH SAAT TERJADI WABAH VIRUS COVID-19 DALAM KARANTINA WILAYAH SESUAI DENGAN UNDANG-UNDANG NOMOR 6 TAHUN 2018 KEKARANTINAAN KESEHATAN - Kasman Siburian; Ondo Puro Hutahaean (Magister Hukum Universitas HKBP Nommensen, 2021)
The determination of the status of the Covid-19 Pandemic by the World Health Organization based on the number of spread of the virus has increased significantly and sustainably globally, this has been responded by the Government of Indonesia by setting the status of the Covid-19 outbreak as a National Disaster on March 14 as stated in the Decree President Number 12 of 2020 concerning the Designation of Non-Natural Disaster for the Spread of Corona Virus Disease 2019 (COVID-19) as a National Disaster. The principle of the unitary state emphasizes the highest power over all state affairs, namely the central government without a delegation or delegation of power to the regional government (local government). Based on the results of the research that has been done, it can be concluded that, considering that there are still problems with coordination, communication and synergy that were felt at the beginning of this pandemic, it is considered to be still lacking. The government should have responded quickly to the pandemic which in turn affected the entire handling process. However, it has been seen that the government is increasingly focused and realizes that coordination is important, one of which is reflected in the existence of a task force and a study of the status of various regions in Indonesia. This is done for the common interest of handling the Covid-19 health emergency.